Traumatic spinal injury: global epidemiology and worldwide volume (2018)
Background Traumatic spinal injury (TSI) results from injury to bony, ligamentous, and/or neurologic structures of the spinal column and can cause significant morbidity and mortality. The global burden of TSI is poorly understood, so we performed a systematic review and meta-analysis to estimate the global volume of TSI. Methods We performed a systematic review through PubMed, Embase, and Cochrane Databases on TSI studies reported from 2000 to 2016. Collected data were used to perform a meta-analysis to estimate the annual incidence of TSI across World Health Organization regions and World Bank income groups using random-effect models. Incorporating global population figures, the annual worldwide volume of TSI was estimated. Results A total of 102 studies were included in the systematic review and 19 studies in the meta-analysis. The overall global incidence of TSI was 10.5 cases per 100,000 persons, resulting in an estimated 768,473 [95% confidence interval, 597,213–939,732] new cases of TSI annually worldwide. The incidence of TSI was higher in low- and middle-income countries (8.72 per 100,000 persons) compared with high-income countries (13.69 per 100,000 persons). Road traffic accidents, followed by falls, were the most common mechanism of TSI worldwide. Overall, 48.8% of patients with TSI required surgery. Conclusions TSI is a major source of morbidity and mortality throughout the world. Largely preventable mechanisms, including road traffic accidents and falls, are the main causes of TSI globally. Further investigation is needed to delineate local and regional TSI incidences and causes, especially in low- and middle-income countries.